TWO HUMANISTIC CONJECTURES IN CATULLUS: 55.17 PAPILLAE AND 61.140 SOLI - Kiss, Dániel (Exemplaria Classica, 2013)
This article investigates the origins of two humanistic conjectures in Catullus. One is papillae at 55.17, which is first attested in Palladio Fosco’s commentary of 1496. However, Palladio was a plagiarist; and both the conjectural phrase lacteolae ... papillae and the transmitted reading lac- teolae ... puellae are echoed in poems by Gioviano Pontano that were written before 1496. The second conjecture that is studied here is soli at 61.140. This has been attrib- uted to the Codex Memmianus (Parisinus lat. 8233) of 1465, where it does not appear. Its earliest attestation may be once again in Palladio’s commentary of 1496. The author of this conjecture remains unknown.